Surgical resection of calcifying nested stromal-epithelial tumor in an adolescent female: A case report. (2020) - Olin, Nicholas; Patel, Ankit; Baker, Susan S.; Hernandez-Alejandro, Roberto
Highlights: Calcifying nested stromal-epithelial tumor is an extremely rare tumor of the liver. Surgical resection with negative margins has demonstrated low risk of recurrence. Surgical approach is dependent upon adequate future liver remnant. ALPSS should be utilized when resection would leave inadequate liver remnant. Abstract: Introduction: Calcifying nested stromal-epithelial tumor (CNSET) is an extremely rare, indolent tumor of the liver of uncertain cellular origin. With only 38 cases reported in the literature, pathogenesis and optimal therapeutic approach are not well characterized. Based on the available literature, the risk of recurrence is low with surgical resection with negative margins. Presentation of case: In this case report, we describe an adolescent patient with CNSET who underwent right trisectionectomy. Discussion: In order to avoid posthepatectomy liver failure, special consideration must be given to the amount of residual liver parenchyma after resection when considering surgical approach. Single stage right trisectionectomy and two stage via associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) were both considered for surgical approach in this case in order to provide sufficient functional liver parenchyma remnant. Conclusion: Given that obtaining negative margins is important in reducing the risk of recurrence, the method of surgical resection utilized is based on the amount of future functional residual hepatic parenchyma.